J07 Guidelines for the oral health of adults with Huntington's disease. (16th November 2010) - Manley (Chairman), G; Carlsson, A; Ahlborg, B; Mårtensson, Å; Nilsson, M B; Lane, H; Balazs, A; Vaalburg, A; Wong, D; van Splunter, P
Abstract : Background: A small group of dental professionals interested in the Oral Health Care of people with Huntington's disease were invited by the European Huntington's Disease Network to provide guidelines for Oral Health. Aim: To provide guidelines which would be an initial part of an evolving process in the improvement of Oral Health. Methods: Guidelines was produced during two meetings based on: A literature review, information from other oral health organizations, the professional clinical opinion of the group. Results: A review of the literature found little evidence in this field. A structured approach described the provision of Oral Health Care under prevention and treatment proposing recommendations related to early, middle and late stages of the condition. The importance of interdisciplinary work was stressed. Outcome: A strategy for oral health was defined. The overall strategy for oral health care will be based on the principles of achieving a disease free, pain free, and safe mouth The standards of care referred to in the guidelines will seek to provide the care and treatment that is no less a standard than an individual that does not have this condition. Such care and treatment will take into account the health and safety of each individual within the context of their condition. Conclusions: The group recognized the need for further quality research. Interdisciplinary work was considered to be a vital part of the guidelines, and it was intended that the group should establish such links.